An analysis of the nonlinear magma‐edifice coupling at Grimsvötn volcano (Iceland). Issue 2 (3rd February 2017) - Got, Jean‐Luc; Carrier, Aurore; Marsan, David; Jouanne, François; Vogfjörd, Kristin; Villemin, Thierry
Abstract: Continuous monitoring of seismicity and surface displacement of active volcanoes can reveal important features of the eruptive cycle. Here high‐quality GPS and earthquake data recorded at Grimsvötn volcano by the Icelandic Meteorological Office during the 2004–2011 intereruptive period are analyzed. These showed a characteristic pattern, with an initial ∼2 year long exponential decay followed by ∼3 year long constant surface displacement inflation rate. We model it by using a one magma reservoir model in an elastic damaging edifice, with incompressible magma and constant pressure at the base of the magma conduit. Seismicity rate and damage were first modeled, and simple analytical expressions were derived for the magma reservoir overpressure and surface displacement as functions of time. Very good fits of the seismicity and surface displacement data were obtained by fitting only three phenomenological parameters. Characteristic time and power strain show maxima from which reference times were inferred that split the intereruptive period into five periods. After the pressurization periods, damage occurring in the third period induced weakly nonlinear variations in magma overpressure and flow, and surface displacement. During the fourth period, the damage dominated and variations became more strongly nonlinear, the reservoir overpressure decreased, and magma flow increased. This process lasted until the power strain reached its second maximum, where instability was generalized. This maximum is a physical limit, the occurrence of which shortly precedes rupture and, eventually, eruption. This analysis allows characterization of the state of the volcanic edifice during the intereruptive period and supports medium‐term prediction of rupture and eruption. Key Points: Analytical expressions for magma reservoir overpressure and surface displacements are derived using a brittle elastic damage model Seismicity and displacements in the volcanic edifice are well fitted by this damage model Pre‐eruptive shear modulus decrease controls magma overpressure. Power strain maxima allow defining times supporting eruption prediction